Idaho politics and government : culture clash and conflicting values in the Gem State - LiCalzi, Jasper M. (Book collections on Project MUSE., 2019)
Examining politics in Idaho through the lens of ideology (i.e., conservative versus liberal) or partisanship (i.e., Democrat versus Republican) does not illuminate the more fundamental dynamics of the state’s political environment. Unlike other states that are divided on partisan or traditional ideological lines, Idaho tends to be divided between its libertarian and communitarian visions of the role of government and the place of the individual in society. --Publisher.